Does one cigarette make an adolescent smoker, and is it influenced by age and age of smoking initiation? Evidence of association from the U.S. Youth Risk Behavior Surveillance System (2011) - Reidpath, Daniel D.; Davey, Tamzyn M.; Kadirvelu, Amudha; Soyiri, Ireneous N.; Allotey, Pascale (Preventive Medicine, 2014)
Objectives: Evidence that age of smoking initiation represents a risk factor for regular smoking in adolescence is complicated by inconsistencies in the operational definition of smoking initiation and simultaneous inclusion of age as an explanatory variable. The aim of this study was to examine the relationship between age, age of smoking initiation and subsequent regular smoking. Methods: A secondary analysis was conducted of the U.S. Youth Risk Behavior Survey 2011. A sex stratified multivariable logistic regression analysis was used to model the likelihood of regular smoking with age and age of smoking initiation as explanatory variables and race/ethnicity as a covariate. Results: After controlling for race/ethnicity, age and age of smoking initiation were independently associated with regular smoking in males and females. Independent of age, a one year's decrease in the age of smoking initiation was associated with a 1.27 times increase in odds of regular smoking in females (95% CI: 1.192-1.348); and similar associations for males (OR: 1.28; 95% CI: 1.216-1.341). Conclusion: While the majority of high school students do not become regular smokers after initiating smoking, earlier initiation of smoking is associated with subsequent regular smoking irrespective of sex or race/ethnicity. These findings have potentially important implications for intervention targeting. © 2013 Elsevier Inc.
Authors not affiliated with University of Hull at time of publication.
Keywords: Smoking; Adolescent; Epidemiology